A prospective randomized controlled trial comparing biphasic cartilage repair implant with microfracture in small chondral lesions of knee: findings at five-year-follow-up - Yao-Yi Kuo; Si-Qi Chiu; Wen-Pei Chang; Chih-Yu Chen; Chih-Hwa Chen; Chen-Kun Liaw; Cheng-Aun Tan; Pei-Wei Weng (Journal of Orthopaedic Surgery and Research)
Abstract Background Full-thickness cartilage defects have a significant impact on the function of joints in young adults, and the treatment of cartilage defects has been a challenge, as cartilage tissue is an avascular tissue. This study aimed to compare the clinical and radiological outcomes of Biphasic Cartilage Repair Implant (BiCRI) and microfracture treatments for knee cartilage defects. Methods This randomized controlled clinical trial enrolled patients with symptomatic knee chondral lesions smaller than 3 cm2. They were randomized to either the BiCRI (n = 11) or microfracture (n = 10) treatment groups. BiCRI or microfracture surgical procedures were performed on the patients, who were subsequently followed for a period of five years. Primary outcome measures included the International Knee Documentation Committee (IKDC) score, Knee Injury and Osteoarthritis Outcome Score (KOOS), Visual Analog Scale (VAS) score, Magnetic Resonance Imaging (MRI) measured cartilage thickness, and the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. Results 21 patients were enrolled, who were subsequently followed for a period of five years. Both BiCRI and microfracture treatments demonstrated significant improvements in IKDC, KOOS and VAS scores, with no significant differences between the two. MRI analysis indicated a significant increase in minimum cartilage thickness with BiCRI treatment (median of difference: 1 mm, P = 0.026)), in contrast to the nonsignificant change in the microfracture group (median of difference: 1 mm, P = 0.102). The MOCART scores revealed a significant increase percentage of isointense signal intensity identical to the adjacent articular cartilage (P = 0.03) in the BiCRI group from the 2-year to the 5-year mark, while the scores remained stable in the microfracture group. Moreover, the BiCRI technique displayed superior performance in graft infill at 5 years (P = 0.008), border integration at 5 years (P = 0.04), surface contour at 2 years (P = 0.04) compared to microfracture. Conclusions Both BiCRI and microfracture treatments showed significant effectiveness in improving clinical outcomes in patients with small symptomatic articular cartilage defects of the knee, with the BiCRI group demonstrating a superior radiological outcome than microfracture, over a five-year period. However, the sample size of our study is relatively small to reach a definite conclusion, and further studies with larger sample size and longer follow up are recommended. Trial registration The trial was registered on ClinicalTrials.gov under the identifier NCT01477008.